Field Emission Properties and Fabrication of CdS Nanotube Arrays - Qian, Xuemin (Springer, 2009)
A large area arrays (ca. 40 cm(2)) of CdS nanotube on silicon wafer are successfully fabricated by the method of layer-by-layer deposition cycle. The wall thicknesses of CdS nanotubes are tuned by controlling the times of layer-by-layer deposition cycle. The field emission (FE) properties of CdS nanotube arrays are investigated for the first time. The arrays of CdS nanotube with thin wall exhibit better FE properties, a lower turn-on field, and a higher field enhancement factor than that of the arrays of CdS nanotube with thick wall, for which the ratio of length to the wall thickness of the CdS nanotubes have played an important role. With increasing the wall thickness of CdS nanotube, the enhancement factorβdecreases and the values of turn-on field and threshold field increase.